Structure of high asymmetric p-n-junction taking into account the charge of movable carriers - Galat, A.B.; Donchenko, A.L. (Radiotekhnika, 2018)
A refined analytical model is proposed for calculating the structure of the spatial charge area of a semiconductor p-n junction with allowance for the spatial charge of movable carriers. The work was carried out in the context of refinement of the analytical estimation of p-n junction recombination current, and also in order to estimate the Schottky model applicability limits when calculating the recombination currents in the spatial charge area of a sharply asymmetric semiconductor p-n junction.